Znaky regionálních inovačních systémů - Maťátková, Kateřina; Stejskal, Jan (Univerzita Pardubice, 2011)
Regional innovation systems (RIS) are become very important instrument of regional policy. This instrument is based on linkages among the institutions in region which are from public and private sector. These linkages are very important because they provide the environment for innovation process which is the main point of RIS. There are defined the main characteristic of the RIS and its specification for Czech Republic in this paper. The core of paper is in the analysis of successfully working RIS existence. This analysis is based on definition of the components of RIS in the Czech Republic. Then is explored the existence of these components in the conditions of Czech Republic and the existence of the linkages among them. At the end of the paper there are summarized the conclusions and recommendations based on the results of analysis.
Keywords: regional innovation system; innovation; region; system; regional development